Edukasi Perpajakan bagi UMKM melalui Klinik Pajak Mahasiswa UKI Paulus sebagai Upaya Meningkatkan Kepatuhan Pajak - Linting, Indriyanti (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The low level of tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia poses a significant challenge to optimizing state revenue. This community service program, implemented through the Tax Clinic of UKI Paulus students, aims to improve MSME tax literacy and compliance through practical and digital approaches. Activities include tax seminars, training in e-Filing and e-Billing, and direct assistance in creating DJP Online accounts and submitting annual tax returns (SPT). Results show that 87% of MSME partners successfully filed taxes independently, and 90% experienced increased understanding of their tax obligations. The program also benefited the Directorate General of Taxes (DGT) by reducing resource burdens, while enhancing students’ professional competencies and reinforcing the university's role in public service. The Tax Clinic has proven effective as a bridge between academic institutions and public fiscal responsibility, particularly in supporting the digital transformation of tax administration. This initiative contributes not only to improving tax compliance but also to student skill development and promotion of accounting programs. The study recommends expanding tax education programs for MSMEs and strengthening collaboration between universities and tax authorities to sustain voluntary compliance and broaden the tax base